(untitled) (Academicia Globe: Inderscience Research, 2023)
This scientific article presents a comprehensive analysis of materials used in the field of flexible and stretchable electronics. The article discusses the importance of flexible and stretchable electronics, provides an overview of various materials used, and explores their properties and potential applications. The literature analysis encompasses recent advancements in materials research, while the methodology section details the experimental techniques employed. The results section presents the findings, followed by a discussion of the implications and challenges associated with the identified materials. The article concludes with a summary of the key points and a list of references for further exploration.